2010
DOI: 10.5114/pg.2010.14141
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the personality features in the illness adaptation process in patients with inflammatory bowel disease

Abstract: Słowa kluczowe: cechy osobowości, temperament, akceptacja, nieswoiste zapalenie jelit. Key words: personality features, temperament, acceptance, inflammatory bowel disease.Adres do korespondencji: Małgorzata Zwolińska-Wcisło, Katedra i Klinika Gastroenterologii i Hepatologii oraz Chorób Zakaźnych, Uniwersytet Jagielloński Collegium Medicum, Kraków, e-mail: mzwcislo@su.krakow.pl Artykuł oryginalny/Original paper StreszczenieCel: W pracy badano czynniki psychologiczne, temperamentalne oraz fizjologiczne u pacjen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Chronic stress is also associated with subclinical inflammation in the intestine [ 17 ]. Other studies showed elevated levels of C-reactive protein (CRP) and pro-inflammatory cytokines in patients with IBD, who were characterised by a high level of neuroticism [ 13 ]. It can be concluded that the combination of neuroticism and a stressful situation may strongly predispose to disease and affect the severity of disease symptoms [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic stress is also associated with subclinical inflammation in the intestine [ 17 ]. Other studies showed elevated levels of C-reactive protein (CRP) and pro-inflammatory cytokines in patients with IBD, who were characterised by a high level of neuroticism [ 13 ]. It can be concluded that the combination of neuroticism and a stressful situation may strongly predispose to disease and affect the severity of disease symptoms [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the personality traits in each stage of the disease (exacerbation/remission) showed insignificant differences in the level of personality traits, namely in neuroticism, openness to experience, conscientiousness, agreeableness, and extraversion at the stage of exacerbation. Another report suggested that patients who presented with CD manifested more neurotic or depressive symptoms, suffered stronger fears, and had lower vitality than UC patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted on diabetics said that acceptance of the disease had a direct impact on adherence to the recommended treatment as well as facing obstacles during coping with the disease (Lickiewicz et al, 2010). Acceptance means accepting, so here it is emphasized that someone must first understand the situation, after which he can accept his condition.…”
Section: Resultsmentioning
confidence: 99%